Capital structure in medium-sized companies in Department of Boyacá, Colombia (2015)
The study of capital structure is one of the financial topics of greatest impact, since among the theories that attempt to explain it,has not yet reached a consensus on the determinants and the behavior of funding decisions in companies. Research on the behavior of capital structure in small and medium size companies, is even more complex issue, since traditional models are mainly applicable to trade on the capital markets or in public interest companies.For this work midsize companies were selected, in the Department of Boyacá in Colombia as study population, applying a model that has been used in similar cases in other countries, in the study has empirically demonstrated preference for equity financing rather than debt, which in turn was preferred by companies with greater volatility in profitability and fastest growing.